CCL3/CCR1 mediates CD14+CD16− circulating monocyte recruitment in knee osteoarthritis progression. Issue 5 (May 2020) - Zhao, X.; Gu, M.; Xu, X.; Wen, X.; Yang, G.; Li, L.; Sheng, P.; Meng, F.
Summary: Objectives: Monocyte-derived macrophages, as the predominant immune cell type that is increased in inflamed synovium, play a vital role during knee osteoarthritis (KOA) progression. However, the mechanisms underlying the recruitment of circulating monocytes to osteoarthritic knees remain uncertain. Based on previous data obtained from plasma, we investigated the contributions of CCL2, CCL3, CCL4 and their cognate receptors in circulating monocyte chemotaxis and KOA development. Methods: Using flow cytometry staining, we characterized the expression patterns of the chemokine receptors in CD14 + CD16 − circulating monocytes from KOA patients and healthy volunteers. The expression of chemokines in synovial fluids, synovium and cartilage was investigated in KOA patients and in patients without KOA. The role of chemokines and their cognate receptors in the chemotaxis of CD14 + CD16 − circulating monocytes was assessed using chemokine neutralizing antibodies (NA) and receptor antagonists in vitro and in vivo . Results: The majority of CD14 + CD16 − circulating monocytes were CCR1-and CCR2-positive. CCL2, CCL3 and CCL4 were elevated in synovial fluid of KOA patients compared with that of controls. The most likely source of these chemokines is inflamed synovium and cartilage in the osteoarthritic knee. The CCL3/CCR1 and CCL2/CCR2 axes showed substantial ability to recruit CD14 + CD16 − monocytes in transwell assays. Similar results were confirmed in a mouse model of collagenase-induced KOA (CIA) in which blocking either the CCL3/CCR1 axis or the CCL2/CCR2 axis reduced synovial hyperplasia and F4/80 + macrophage infiltration. Conclusions: Our findings suggested that, analogous to the CCL2/CCR2 axis, CCL3 produced in osteoarthritic knees can chemoattract circulating monocytes to the inflamed synovium through CCR1.